E-government: Performance of the public sector from a comparative perspective - Morales-Urrutia, Ximena (2020)
This paper aims to provide an analysis of e-government in selected countries, both conceptually and empirically. In order to do this, a bibliographical review pertinent to the subject matter of the study is taken as a starting point. Subsequently, the work is completed with an analysis of the performance and main characteristics of this phenomenon. The data analyzed come mainly from official sources, specifically from the E-Government Development Index survey for the period 2008-2018. On the basis of this analysis, we attempt to draw provisional conclusions on e-government performance in countries that have adopted this trend. © 2020, Associacao Iberica de Sistemas e Tecnologias de Informacao. All rights reserved.